ANALISIS STRUCTURAL EQUATION MODELING PADA PENGARUH KEBIASAAN MENGAKSES FACEBOOK TERHADAP KUALITAS HIDUP DAN PRESTASI AKADEMIK MAHASISWA - Nalim Nalim (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2014)
This study tried to determine the effect on quality of life Facebook and students' academic achievement. A total of 210 samples were taken from three universities with proportional multistage random sampling method, while data analysis was conducted using Structural Equation Modeling (SEM) with software lisrel 8.80 (student version). The results showed, although according to the investigators alleged that Facebook had a negative impact on quality of life, but the effect was not significant. This is evident from the t value of -1.90 (less than 1.96). Similarly, the structural equation generated, quality of life and Facebook together provide significant influence on academic achievement (with values of t are respectively 0.69 and -0.92). Keywords: structural equation modeling, custom facebook access, quality of life, student academic achievement